2012
DOI: 10.1007/s10692-012-9381-0
|View full text |Cite
|
Sign up to set email alerts
|

Modification of natural fibers and leathers by polymer fillers based on a polyquaternary salt

Abstract: We have synthesized a polymeric quaternary ammonium salt of β-methacryloylethyl-Ndimethyl(allyl)ammonium bromide (β-MAEDAB) based on reaction of N,Ndimethylaminoethylmethacrylate with allyl bromide. We have developed a water-soluble polymeric composition based on the polyquaternary salt of β-MAEDAB combined with glycerol for treatment of natural fibers (cotton and wool) and leather (cowhide and goatskin). We have studied the physical and chemical properties of aqueous solutions of the polymeric composition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It is based on the reverse exchange of ions of the liquid and solid phases. It differs from other methods in its low cost, selectivity, lack of formation of unnecessary substances in excess quantities, and the possibility of extracting metals [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the reverse exchange of ions of the liquid and solid phases. It differs from other methods in its low cost, selectivity, lack of formation of unnecessary substances in excess quantities, and the possibility of extracting metals [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the most ideal material of leather imitation, synthetic leather has poor water vapor permeability and moisture permeability because fewer hydrophilic groups exist in the microfiber and it has narrow gaps between microfiber bundles and PU [1][2][3][4][5]. Thus, further research is needed to improve the wearing comfort and hygienic property of the microfiber synthetic leather [6][7][8][9][10]. Studies have shown that the most effective modification method is to increase the internal active groups of microfiber synthetic leather.…”
Section: Introductionmentioning
confidence: 99%